Calculation of Power Losses in Primary Distribution Line 20 kV with Point-To-Point Sequential Method - Ervianto, Edy; M, Noveri Lysbetti; Nurhalim, Nurhalim; Amri, Rahyul (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2018)
All electric power cannot be distributed well to consumers caused of Power-Losses caused by technical and untechnical losses. Power-Losses caused by technical issue in Distribution-Network caused-by resistance substance in conductor which is permanent. An ideal conductor must not has resistance, but in reality, every matter has resistance towards electric. Main possibility of Power-Losses in Distribution-Network is natural situation of network itself, such-as length of network always tends to increase. Aim of research is to calculate Power-Losses that absorbed by conductor in Primary-Distribution-Line-20kV with Point-to-Point Sequential Method while it loaded. The highest Power-Losses occurred in conductor OL–Melati Street with RST-Phases are 4766,441Watt, 4335,654Watt, 4003,747Watt, respectively. The biggest Power-Losses is on conductor of OL–Melati Sreet, whereas current and resistance are bigger than others. Total Power-Losses absorbed-by conductor is 72135.99Watt that the smallest losses, obtained from measuring of used real load on each Distribution-Transformer. Percentage of Power-Losses towards used power on Lobak-Feeder 1.3177%.